Wolff‐Parkinson‐White Syndrome and pheochromocytoma. Issue 2 (13th August 2013) - Mungasuvalli, Nagaraj Channappa; Bevinaguddaiah, Yatish; Seenappa, Vinayak Pujari; Chikkapillappa, Manjunath Abloodu
Summary: Wolff‐Parkinson‐White syndrome is a cardiac conduction disorder. Management of a patient with WPW syndrome can be compounded when it is associated with pheochromocytoma. We describe the successful perioperative management of a rare case of pheochromocytoma associated with WPW syndrome. We reduced the potential risk of WPW syndrome associated arrythmias by ablation of the aberrant conduction tract prior to surgery.